Climate and energy targets under Europe 2020 strategy and their fulfillment by member states - Gontkovičová, Barbora; Duľová Spišáková, Emília (Frontiers in Environmental Science, 2023)
European member states have taken several systematic steps on the way to become low-carbon and resource-efficient economies since the adoption of the Europe 2020 Strategy. The long-term targets in the field of climate and energy challenges is currently being continued and developed through the sustainable development goals (SDGs) of the 2030 Agenda. In order to assess the current situation and progress in the given area, it is necessary to consistently analyze the results that the member states have achieved during the validity of the Europe 2020 Strategy. Therefore, the aim of the article is to analyze and assess the degree of fulfilment of Europe 2020 targets by EU member states in the field of the environment with a subsequent link to the targets of the 2030 Agenda. We compared the values of the selected indicators (Share of renewable energy in gross final energy consumption (RER), Final energy consumption (FEC), Primary energy consumption (PEC) and Net greenhouse gas emissions (GHG)) in the EU Member States with the national goals of the selected countries by application of multivariate comparison methods, namely the ranking method, the scoring method and the distance method. Among the countries that achieved the best results in the evaluation were Greece, Romania and Estonia. On the other hand, in the sample of countries, there were four, namely France, Ireland, Austria and Belgium, which did not meet the targets and based on the prediction, they will not achieve them even by 2025.